Advancing our understanding of immigrants’ trust in police: the role of ethnicity, immigrant generational status and measurement - Ali, Mohammed M. (Policing and society, 2023)
Studies of immigrant populations point to numerous immigrant-specific factors that may explain their level of trust in police. Yet research on immigrants’ trust in police remains sparse, and available studies present contradictory findings. Some studies find that immigrants are more trusting of police than non-immigrants, while other studies find immigrants are less trusting of police. We argue that these contradictions can be explained by three factors: (1) how trust is measured; (2) immigrants’ ethnic group (e.g. minority vs non-minority); and (3) immigrants’ generational status (i.e. 1st vs. 2nd generation immigrant). To address these contradictions, we draw on survey data from 903 immigrants living in Sydney, Australia. We examine the relationship between ethnicity, immigrant generational status and various measures of trust in police. We find when trust is measured as an overarching orientation, minority immigrants tend to distrust police more than non-minority immigrants, and that 2nd generation immigrants are more distrusting than 1st generation immigrants. However, these findings vary when measuring trust multi-dimensionally and when accounting for the interaction between ethnicity and generational status. Implications for immigrant research and police practice are discussed.